The Sequence of Intracranial Radiotherapy and Systemic Treatment With Tyrosine Kinase Inhibitors for Gene-Driven Non-Small Cell Lung Cancer Brain Metastases in the Targeted Treatment Era: A 10-Year Single-Center Experience - Yang, Siran; Xiao, Jianping; Liu, Qingfeng; Zhang, Ye; Bi, Nan; Huang, Xiaodong; Chen, Xuesong; Wang, Kai; Ma, Yuchao; Deng, Lei; Wang, Wenqing; Zhao, Ruizhi; et al. (Frontiers in Oncology, 2021)
Purpose: The high intracranial efficacy of targeted therapeutic agents poses a challenge in determining the optimal sequence of local radiation therapy (RT) and systemic treatment with tyrosine kinase inhibitors (TKIs) in non-small cell lung cancer (NSCLC) patients with brain metastasis (BM). Therefore, we conducted a cohort study to elucidate the appropriate treatment strategy, either upfront RT or deferred RT including a toxicity assessment, in these patients. Patients and Methods: We retrospectively evaluated patients with gene-driven BMs from a single institution and divided them into deferred and upfront RT groups. Survival was estimated using a log-rank test. Intracranial progression was estimated using Fine-Gray competing risks model. Cox proportional hazards regression was performed for multivariable analysis in the entire group and subgroups. Results: Among the 198 eligible patients, 94 and 104 patients received deferred and upfront RT, respectively. The upfront RT group showed a lower intracranial progression risk with an adjusted sub-distribution hazard ratios of 0.41 (95% CI, 0.30 – 0.57) than did the deferred RT group (median intracranial progression-free survival [iPFS], 19.9 months vs. 11.1 months; P < 0.001). The median overall survival (OS; 43.2 months vs. 49.1 months, P = 0.376) and BM-specific survival (92.1 months vs. 82.9 months, P = 0.810) after salvage therapy were not significantly different between the upfront and deferred groups. Among patients with progressed extracranial disease, the deferred RT group showed significantly better OS than did the upfront RT group (44.0 vs. 28.1 months, P = 0.019). Grade 3–4 treatment-related adverse events were rare, and similar toxicities were observed between the two groups. Conclusion: Compared to the deferred RT group, the upfront RT group achieved longer iPFS and similar survival outcomes in most patients with gene-driven NSCLC BM, although patients with progression of extracranial disease might benefit from deferred RT. Both groups showed well-tolerated toxicities.